Analisis Break Even Point Sebagai Alat Perencanaan Laba Jangka Pendek Pada CV. Abadi Bata Pangkalan Balai - Sri Sutandi; Lia Sari; Masnoni; Hilwa Anggraini; Irsan (JURNAL EKOBIS Kajian Ekonomi dan Bisnis, 2019)
CV. Abadi Bata Pangkalan Balai is a company engaged in the production and marketing of bricks. To get the data the author uses interviews, observation and library research. Based on the data and information obtained, it is known that the company has not classified the costs experienced by the company into fixed costs and variable costs, so the company has not been able to calculate the break even point and margin of safety which the company can use as a company profit planning tool. Based on the literature review, the authors analyze cost classification, break even point calculation, profit planning and margin of safety. From the analysis carried out, the authors can conclude that in profit planning using break even point calculations, data on fixed costs and variable costs is needed. Furthermore, break even point analysis can be used to predict costs that will occur to expect the achievement of certain profits. The author also suggests that the company's management consider using break even point analysis as a profit planning tool and the company should make a margin of safety calculation so that the company can know how much sales volume is safe for the company so that it does not suffer losses.